Bariatric Surgery in the Peritransplant Period. Issue 4 (1st May 2021) - Pomenti, Sydney; Mehta, Sanket; Guo, Averill; Wattacheril, Julia
Abstract : Watch a video presentation of this article Watch the interview with the author